Scientific production associated with spending and investment in research in peruvian universities - Moquillaza-Alcántara, Victor Hugo (2019)
Introduction. The scientific production of Peru is low in relation to other countries; the impact of investment in such production at the national level is unknown. Objective. To evaluate the association between spending and investment in research and scientific production on health issues in peruvian universities during 2015. Methods. Observational study of secondary sources analysis of the I National Research and Development Census to Research Centers of the National Council of Science, Technology and Technological Innovation (Concytec), from where Peruvian universities and publications in the area of science were selected. health. The incidence of crude and adjusted relative risk (IRR) was evaluated to determine the degree of association. Results. There is a significant association between the scientific production and the remuneration of the research teachers (IRR: 0,998, p<0,01), remuneration to the support staff (IRR: 1,023, p<0,01), fees to external consultants (IRR : 0,991, p<0,05), purchase of other services (IRR: 1,003; p<0,01) and investment in buildings (IRR: 0,998; p<0,01). Conclusions. The remuneration of research faculty, support staff, external consultants, purchase of other services and investment in buildings, is associated with the highest scientific production in health issues in Peruvian universities.